Convenções da Organização Internacional do Trabalho e sua inter-relação com os Estudos da Tradução - Silva, Adriane Moura e (2019)
The purpose of this research is to study some of the ILO´s Conventions in order to verify a particular textual phenomenon: their translation. The general objective of the research is to find elements that indicate the interrelationship between Translation Studies and the ILO´s Conventions ratified by Brazil. The specific objectives are: to highlight the contribution of multidisciplinarity in the Studies of Legal Translation; to ascertain which historical factors have interfered in the translation of the aforementioned international Conventions; to identify how the translation of these documents is done and whether there are any text(s) used as a model(s); to analyze the equivalence of the versions of the Conventions in Brazilian Portuguese language compared to other versions in the official languages (English, French), as well as any existing version in Portuguese of Portugal; to indicate aspects of the translation of international treaties and the role of the specialized translator. Regarding the approach, objectives and technical procedures, the research is qualitative, exploratory and bibliographic (SILVA; MENEZES, 2005). The methods used are deductive and dialectical (SILVA; MENEZES, 2005) and the theoretical framework took into account the teachings of Duarte, Rosa e Seruya (2006), Cao (2010), Gambier e Van Doorslaer (2011), Prieto Ramos (2011; 2014; 2017), and Lambert (1985; 2017). As result, it could be seen that there is the influence of several languages taken into consideration for the preparation of the normative text in Brazilian Portuguese. In the first (1919-1939) and in the second period (1945-1970) the French language played a prominent role used as a parameter by the Brazilian translator. In the third period (1970-2000) and in the contemporary period (2000-2019), the use of more than one model is observed, highlighting the versions in English and Portuguese, without excluding interference coming from the French structure. Regarding the aspects of legal translation, the diversity of its categorization was observed, verifying the functionality of Legal Hermeneutics and Comparative Law by offering interpreting techniques to the translator, who should seek multidisciplinary elements for the best performance of his function.